Political Governance and Economic Growth: Institutional Analysis of Russian Experience - I. A. Mankovsky (Вестник Российского экономического университета имени Г. В. Плеханова, 2025)
Dependence of the economic system efficiency on the quality of managerial (political) decision-making, institutional environment of national economy developed on their basis, the level of economic plan implementation and the degree of economic system readiness to function in conditions of external challenges was demonstrated by interdisciplinary analysis. The period from 2018 to 2024 was analyzed, which is explained by the political process being realized in Russia, the fixed six-year cycle of strategic planning and exogenous factors arose within this period of time that influenced seriously the efficiency of national economy. The article carried out retrospective analysis of the most important factors of Russian political system transformation, which affected the content of institutional environment of national economy and hence, the trend and intensity of economic development, which, according to the author, could help find mutual dependence of economic development and political transformation in society, rise trustworthiness of institutional analysis of Russian society and economic policy elaborated on its foundation. The author analyzed the impact on the national economy dynamics on the part of the essential (program) documents identifying trends, goals and objectives of the social and economic development of Russian society introduced into the structure of national economy institutional environment within the period being studied and found the reasons for their inadequate implementation. The article investigates the standing of national economy stipulated by technological dependence of the industrial sector on economy of unfriendly states, which deteriorated after 2022. It was shown that political decisions aimed at overcoming technological dependence and providing technological sovereignty of Russia could not reach the desired result. Some reasons for their improper execution have been identified. A conclusion was drawn about necessary modernization of national economy institutional environment in the direction of cutting departmental and municipal rule-making in the field of economic development and elaboration on the basis of inter-disciplinary institutional analysis of the Strategy of Social and Economic Development of the Russian Federation for the long-term perspective as a unique economic plan.